International Federation of the Red Cross and Red Crescent Societies Global Onboarding - Monteforte Sasseron, Bethania (Digital Repository of Theses, 2024)
The objective of this research was to develop a comprehensive global onboarding programme for the IFRC, with the aim of addressing the fragmented processes that were observed across various regions. A mixed methodology was employed, comprising surveys, interviews and focus groups. The 313 participants included newcomers, managers, human resources stakeholders, global leaders within the IFRC and other organisations. The findings provided an understanding of the current onboarding best practices, challenges and areas for improvement. The study highlighted the necessity for a standardised process, centralised information storage, social integration, connection with the Fundamental Principles and comprehensive support for all onboarding participants. The solution was developed using the Agile methodology and became the IFRC Global Onboarding Portal, a dedicated SharePoint intranet site that serves as a digital solution for the centralisation of resources, the facilitation of real-time updates, and the fostering of a sense of community during onboarding. It comprises a wide range of resources, all of which have been developed in accordance with the IFRC brand assets. These include manuals, checklists, links to both internal and external sources, libraries and a dedicated page for the Fundamental Principles. The portal facilitates access to essential resources, platforms and e-learning solutions, as well as a communications strategy that ensures uniform and high-quality onboarding for all, regardless of geographical location. The site analytics demonstrated a consistently high volume of traffic and user engagement, indicating the site's efficacy and relevance to its users since its launch in November 2023. Future research recommendation should focus on conducting longitudinal studies to monitor the long-term impacts of the programme and explore the integration of new features such as artificial intelligence and site user feedback, ensuring continuous improvements. In conclusion, the IFRC Global Onboarding programme was developed based on comprehensive research and in alignment with the IFRC’s mission. The framework provides a comprehensive structure to improve the onboarding experience and offer support to newcomers, their assigned buddies, and the onboarding team. The programme enhances the IFRC’s capacity to respond effectively to humanitarian needs, fostering a unified, efficient and resilient organisation.